Asuhan Keperawatan pada Pasien Post Craniotomy et Causa Tumor Intrakranial dengan Intervensi Range of Motion: Studi Kasus di Intensive Care Unit RSU Royal Prima Medan Tahun 2026 - Nurhayatika Sidabutar; Julia Fransisca Sinaga; Sarina Lahagu; Endah Juni Sastri Telaumbanua; Yosefhine Christine S. Sihombing; Kristina L Silalahi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Post-craniotomy patients with intracranial tumors commonly experience respiratory instability, impaired cerebral perfusion, decreased consciousness, and immobilization requiring intensive nursing care in the Intensive Care Unit. This study aimed to analyze the implementation of passive Range of Motion (ROM) intervention in improving respiratory rate, oxygen saturation, and physiological responses in post-craniotomy patients. The study used a descriptive qualitative case study approach involving a 58-year-old male patient treated in the ICU of RSU Royal Prima Medan in March 2026. Data were obtained through clinical observation, respiratory assessment, vital sign monitoring, and medical record documentation using SDKI, SIKI, and SLKI standards. The findings indicated clinical improvement characterized by decreased respiratory rate, stable oxygen saturation, reduced ronchi and bloody sputum, lower restlessness, and improved activity tolerance. Passive ROM intervention contributed to physiological stabilization and prevention of immobilization-related complications during intensive care. These findings demonstrate that evidence-based nursing care supports neurocritical recovery and postoperative rehabilitation outcomes in post-craniotomy patients.